(untitled) (Advancements in Homeopathic Research, 2025)
Eczema is one of the most common skin disorders, where the lesion tends to disseminate, spreading rap idly and distantly from its point of origin. Palmoplan tar dermatitis, an intense, pruritic, relapsing medical condition requiring long term treatment associated with dryness, painful fissures and scaling of palm, sole or both leading to lichenification. Keeping in mind the several hazardous effects of conventional treatment where various steroidal ointments and other calcineurin inhibitors are used, homoeopathy promises to treat the sick in a rapid, gentle, perma nent way. The presented case report intends to record individualised homoeopathic constitutional medicine based on totality of symptoms curing a case of pal moplantar dermatitis with Silicea terra 200 single dose with no recurrence of symptoms.